2019
DOI: 10.1532/hsf.2499
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive CABG or Hybrid Coronary Revascularization for Multivessel Coronary Diseases: Which Is Best? A Systematic Review and Metaanalysis

Abstract: Objectives: Minimally invasive coronary revascularization (MICR) involves minimally invasive direct coronary artery bypass grafting (MIDCAB) and robotic-assisted coronary artery bypass grafting (RCABG), and hybrid coronary revascularization (HCR) aims to combine MICR/RCABG on left anterior descending (LAD) and percutaneous coronary interventions (PCI) on non-LAD lesions. We performed a systematic review and metaanalysis to compare clinical outcome after MICR and HCR. Methods: A metaanalysis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…Before jumping into discussions about comparisons between outcomes of HCR and PCI, we should first ask ourselves if HCR is superior (or at least comparable) to CABG surgery, considered to be the best option for MVD. Two recent meta-analyses [6] , [7] shed some light on this subject. Wang et al [6] conducted a meta-analysis with 23 studies including 10,468 patients (2403 underwent HCR and 8065 patients underwent traditional CABG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before jumping into discussions about comparisons between outcomes of HCR and PCI, we should first ask ourselves if HCR is superior (or at least comparable) to CABG surgery, considered to be the best option for MVD. Two recent meta-analyses [6] , [7] shed some light on this subject. Wang et al [6] conducted a meta-analysis with 23 studies including 10,468 patients (2403 underwent HCR and 8065 patients underwent traditional CABG.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term results showed no significant difference between the HCR and CABG techniques. Guan et al [7] performed a systematic review and meta-analysis to compare clinical outcomes after HCR and minimally invasive coronary revascularization (including minimally invasive direct coronary artery bypass grafting and robotic-assisted coronary artery bypass grafting). Their study included 8 observational studies with 1084 cases of HCR and 2349 cases of minimally invasive coronary revascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2-6) Equally, most of the studies have also confirmed that compared with other techniques of revascularization, HCR is associated with similar 30-day mortality. (2)(3)(4)(5)(6) The evidence on reduction in rates of atrial fibrillation (AF) is not very strong with other studies and meta-analysis reporting no difference in AF rates between HCR and other techniques of revascularization. (4,7) The shorter ICU and overall hospital length of stay reported in this study is also supported by several other studies.…”
mentioning
confidence: 99%
“…(4,7) The shorter ICU and overall hospital length of stay reported in this study is also supported by several other studies. (3)(4)(5)(6) However, the definition of what constitutes operative time and hospital length of stay needs further discussion. HCR consists of two distinct procedures -CABG and PCI.…”
mentioning
confidence: 99%